Routing Algorithm Based on Area Division Management of Node in Wireless Sensor Networks - Gao Wei; Song Yan; Shuping Fan (Universitas Ahmad Dahlan, 2015)
In order to reduce the communication overhead among sensor nodes, a routing algorithm is proposed based on zoning management nodes. The algorithm defines the calculation method of the network partition radius after nodes deployment, and divides monitored area according to the radius meanwhile layouts one management node in each partition. Then nodes’ communication cost is calculated based on the distance among nodes as well as nodes’ energy, and finishes the selection of routing nodes based on the cost. Finally, using the Matlab simulation environment, the parameters impacting the optimal partition radius are discussed, and the proposed routing algorithm is compared with existing algorithms. Theoretical analysis and experimental results show that the proposed algorithm is more balanced on nodes energy consumption. The algorithm reduces network traffic overhead while extends the lifetime of the network.